Impact of population aging on the burden of vaccine-preventable diseases among older adults in the United States - Sandra E Talbird; Elizabeth M La; Justin Carrico; Sara Poston; Jean-Etienne Poirrier; Jessica K DeMartino; Cosmina S Hogea (Taylor & Francis Group, 2021)
Despite vaccination recommendations, the burden of vaccine-preventable diseases remains high in older adults in the United States (US), contributing to substantial morbidity, mortality, and health care resource use and costs. To adequately plan for health care resource needs and to help inform vaccination policies, burden of disease projections that account for population aging over the coming decades are needed. As a first step, this exploratory study projects the burden of influenza, pertussis, herpes zoster, and pneumococcal disease in adults aged 50 y and older in the US, using a population-based modeling framework with separate decision trees for each vaccine-preventable disease. The model uses projected population estimates from the US Census Bureau to account for changes in the US population over time and then calculates expected numbers of cases and associated costs for each disease, keeping current estimates of age-specific disease incidence, vaccine coverage, and efficacy constant over time. This approach was used to focus the exploratory analysis on the burden of disease that may be expected due to population changes alone, assuming that all else remains unchanged. Due to population growth and the shifting age distribution over the next 30 y, the annual societal economic burden for the four vaccine-preventable diseases is projected to increase from approximately $35 billion to $49 billion, resulting in cumulative costs of approximately $1.3 trillion, as well as more than 1 million disease-related deaths. Given such notable burden, further efforts to increase vaccination coverage and effectiveness in older adults are needed.